"Cause That's the Only Skills in School You Need": A Qualitative Analysis of Revenge Goals in Poor Urban Youth. (January 2016) - Jäggi, Lena; Kliewer, Wendy
Revenge goals are correlated with maladjustment, and retaliation is a factor driving youth violence. However, revenge might be an important social tool adolescents use to achieve (self-)justice in environments where institutionalized interventions from authorities such as teachers or police are limited. This qualitative secondary analysis of 50 revenge scenarios from a larger study ( N = 358 youth-caregiver dyads) expands one-dimensional knowledge from closed-answer vignettes to the rich real-world experiences of youth (aged 10-16; 30 boys, 20 girls), from an urban community sample. Ten patterns of qualitative differences in cognition and emotion of revenge scenarios emerged and are discussed within the revised model of social information processing (SIP). Importance of reputation, confidence in non-violent solutions, and the influence of intense emotions were among the themes. Gender differences and implications for prevention are discussed.